2014
DOI: 10.1590/1089-6891v15i425797
|View full text |Cite
|
Sign up to set email alerts
|

Análises coproparasitológicas de aves silvestres cativas

Abstract: Na maioria dos casos de parasitismo em aves cativas não há expressão de sinais clínicos. Esse fato aponta a importância da realização de exames parasitológicos frequentes nesses animais. O objetivo do presente trabalho foi realizar exames coproparasitológicos para monitorar as infecções parasitárias nas aves cativas no Parque Municipal Danilo Galafassi (Zoológico Municipal de Cascavel-PR), projeto aprovado pela Comissão de Ética e Bem-estar Animal (CEBEA) do Campus Palotina-UFPR, protocolo nº 29/2010. Foram an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 6 publications
1
20
0
18
Order By: Relevance
“…It is important to note that the differences in positivity rates found in distinct studies may be attributed to the sensitivity and specificity of the copromicroscopic technique, as well as the parasitic load of each animal (SANTOS et al, 2008;COSTA et al, 2010). In addition, proper sample collection and conservation are essential to avoid misdiagnosis, and consequently different results (SNAK et al, 2014). The parasites most frequently found in this study were Ascaridia sp., Capillarinae, Trichostrongylidae and coccids.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…It is important to note that the differences in positivity rates found in distinct studies may be attributed to the sensitivity and specificity of the copromicroscopic technique, as well as the parasitic load of each animal (SANTOS et al, 2008;COSTA et al, 2010). In addition, proper sample collection and conservation are essential to avoid misdiagnosis, and consequently different results (SNAK et al, 2014). The parasites most frequently found in this study were Ascaridia sp., Capillarinae, Trichostrongylidae and coccids.…”
Section: Introductionmentioning
confidence: 76%
“…The overall positivity rate (69%; 22/32) reported here was higher than rates detected in previous studies. For instance, a study conducted in the state of Paraná, Brazil, reported a prevalence of gastrointestinal parasites of 54% (127/228) in fecal samples of wild birds using the Hoffman sedimentation technique and the Willis flotation method as diagnostic tools (SNAK et al, 2014). Conversely, a low positivity rate (19.6%; 40/207) was detected in exotic birds in the state of São Paulo (MARIETTO-GONÇALVES et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prevalência de parasitos em mamíferos de cativeiro varia conforme a região em que o animal se encontra, o clima do ambiente, o manejo sanitário empregado, a profilaxia e o tratamento utilizado para determinada doença [18].…”
Section: Discussionunclassified
“…Em cativeiro, os animais tornam-se mais vulneráveis às enfermidades, já que sua exposição às infecções na natureza é mínima e limitada. Algumas doenças podem deixá-los debilitados ou até mesmo devastar populações [18]. O exame parasitológico de fezes em animais de zoológicos é um recurso diagnóstico bastante relevante por ser capaz de fornecer informações sobre a fauna helmíntica própria de determinada espécie ou daqueles parasitos que podem ser transmitidos ao homem, além de fornecer subsídios a respeito das características do ambiente em que esses animais vivem.…”
Section: Introductionunclassified